Fenomena Penggunaan Shopee Paylater: Dampak Gaya Hidup Hedonisme Sebagai Pemicu Perilaku Konsumtif Masyarakat Kota Binjai - Syazwina Nadhira Nadhira; Elida Elfi Barus (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The development of financial technology has introduced various digital payment innovations, including the Buy Now Pay Later (BNPL) feature provided by Shopee Paylater. This study aims to analyze the influence of Shopee Paylater usage and a hedonic lifestyle on the consumptive behavior of the people in Binjai City. This research is quantitative with a causal associative approach. Data were collected through a survey of 150 respondents in Binjai City, selected via purposive sampling with criteria including active Shopee Paylater users. The analytical method used is multiple linear regression processed through SPSS. The results show that Shopee Paylater usage has a significant positive effect on consumptive behavior, driven by ease of access and low